Elements of of happiness and lasting well-being in Hajj - Ayob, Salahuddien; Mohd Hashim, Intan Hashimah; Ahmad Hatta, Zulkarnain; Abdul Ghani, Noraida; Abdul Rahman, Shukran; Md Saad, Zarina; Sulong, Jasni; Mohd Mahudin, Nor Diana (2013)
Most people generally aim to obtain happiness and everlasting well- being in their life. One of the aim of positive psychology is to understand this nature of happiness. Seligman (2011) believed that long lasting wellbeing comprised of five essential elements: positive emotion, engagement, positive relationships, meaning, and accomplishment. Positive Psychology, which has focus on the conditions and process that contribute towards the flourishing and optimal functioning of people, groups, and institutions, must base its research around the five elements. Hajj is a once in a lifetime pilgrimage obliged to all adult Muslims who are physically and financially capable. It is a communal act of worship, committed individually and yet, by being in ihram and completion of sets of rituals, emphasizes equality and unity among all Muslims. Previous psychological research on Hajj is scant. However, it was reported that despite significant health and safety risk associated with hajj, pilgrims have reported positive experiences and psychological changes after Hajj (Wolfe, 1997; Clingingsmith, Khwaja & Kremer, 2009). This paper proposes how Hajj as a potential positive institutions may have the five elements in that it require the pilgrims to have some level of positive emotions, a sense of engagement, with opportunities to develop positive relationships, meanings and sense of accomplishment within the rituals. Plan for further research on these variables is discussed.